The relationship between loneliness and school dropout - Ifeoluwa Adenuga; Betul Tuncer; Kristi Baerg MacDonald; Julie Aitken Schermer (Current Research in Behavioral Sciences)
Previous research has focused on demography, social factors, and school achievement as determinants of school dropout. The present study looks deeper into the subjective experiences of students, with a particular interest in the roles of loneliness and interpersonal relationships in school dropout. A questionnaire was completed by undergraduate university students (255 men, 246 women, 1 other), containing a measure of loneliness, as well as questions concerning friendship, social interaction, and thoughts of dropping out of high school and first year university. Results showed that loneliness was a strong predictor for the dropping out of high school and university questions, increasing the odds by two and a half times. In addition, thinking about dropping out of high school significantly predicted thoughts about dropping out of university. Although this study examined thoughts about leaving school and not actually dropping out, the results do demonstrate how loneliness is negatively impacting students.